Trends of Course Based Undergraduate Research Experiences: A Bibliometric Analysis - Lukman Hadi; Ahmad Mudzakir (Proceeding of the International Conference on Global Education and Learning, 2024)
This study aims to provide a bibliometric analysis of course-based undergraduate research experience from 2010-2023. Data were extracted from the Scopus database and analyzed using VOSviewer. A total of 67 related publications were analyzed and mapped. According to bibliometric analysis, course-based undergraduate research experience, inquiry-based learning, and upper-division undergraduate become the center of the topic in the study of course-based undergraduate research experience in chemistry. It also shows that collaborative/cooperative learning, discovery learning, problem-solving/decision-making, first-year undergraduate, organic chemistry, and chemical education research. are among the novel and emerging topics in course-based undergraduate research in chemistry. This research is expected to provide a better understanding of the challenges and opportunities of studying course-based undergraduate research experience in chemistry.